2011
DOI: 10.1051/alr/2011139
|View full text |Cite
|
Sign up to set email alerts
|

Use of calcein to estimate and validate age in juveniles of the winged pearl oysterPteria sterna

Abstract: -Determining age is an important step when assessing growth, mortality, and yield of cultivated and wild populations, but studies linking shell growth marks in the pearl oyster Pteria sterna with the age of individuals are lacking. Thirty juveniles (20.0 ± 1.2 mm shell height), collected from a winter spatfall, were marked with the fluorochrome calcein and kept in the field in culture containers. After day 16, the juveniles were cleaned and their shells cut along the sagittal axis to determine periodicity of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Several chemical markers like strontium, calcein, and alizarin red were used for shell increment determinations through marking experiments (Fujikura et al 2003;Riascos et al 2007;Herrmann et al 2009). A fluorescent compound easy to use and detect, polyanionic calcein, has been widely used as a growth marker (Kaehler and McQuaid 1999;Riascos et al 2007: Herrmann et al 2009Cáceres-Puig et al 2011). The calcein solution is incorporated into the mantle cavity where it deposits a fluorescent line, visible on suitably prepared shell sections under blue light (Wilson et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Several chemical markers like strontium, calcein, and alizarin red were used for shell increment determinations through marking experiments (Fujikura et al 2003;Riascos et al 2007;Herrmann et al 2009). A fluorescent compound easy to use and detect, polyanionic calcein, has been widely used as a growth marker (Kaehler and McQuaid 1999;Riascos et al 2007: Herrmann et al 2009Cáceres-Puig et al 2011). The calcein solution is incorporated into the mantle cavity where it deposits a fluorescent line, visible on suitably prepared shell sections under blue light (Wilson et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Once laid down in the CaCO 3 growth-band, calcein emits a lime-green fluorescent color when exposed to blue light (Wilson, Beckman, & Dean, 1987;Heilmayer et al, 2005;Tada, Fujikura, Oguri, Kitazato, & Tanabe, 2010;Linard et al, 2011), which was shown highly advantageous and appropriate, over other methods, in aiding the determination of growth increments after initial calcein mark incorporation into the growingedge in certain bivalves (Kaehler & McQuaid, 1999;Fujikura et al, 2003;Heilmayer et al, 2005;Riascos, Guzman, Laudien, Heilmayer, & Oliva, 2007;Riascos, Heilmayer, Oliva, Laudien, & Arntz, 2008;Herrmann et al, 2009;Cáceres-Puig, Huato-Soberanis, Melo-Barrera, & Saucedo, 2011).…”
mentioning
confidence: 99%